With All Our Strength - Cheshmak Farhoumand-Sims (International Institute of Islamic Thought, 2005)
Anne Brodsky’s With All Our Strength provides an ethnographic study of the Revolutionary Association of the Women of Afghanistan (RAWA). This organization was founded in 1977 by the enigmatic Meena as “the first independent feminist women’s organization in Afghanistan, whose sole purpose and aim was the advancement and equality of Afghan women” (p. 43). RAWA’s main vehicle of empowerment is education, through literacy and political consciousness, and its vehicles for promoting these tasks are literacy classes and Payam-e-Zan, a quarterly political magazine (published in Dari and Pashtu) that includes political commentaries on a wide range of issues relating to Afghanistan. The author describes RAWA as a humanitarian and political women’s organization that has operated in Afghanistan and Pakistan since its founding in 1977. She provides a good review of its philosophy and workings through an impressive number of interviews and personal observations gained while living and traveling with RAWAmembers. Her analysis offers insight into Afghanistan’s patriarchal culture, as well as the customs and traditions that have impacted its women. She presents readers with an excellent analysis of the events that led to the conflict in Afghanistan, discusses the country’s situation since the regime change of 1979, and highlights the humanitarian cost of war, focusing on the conflict’s impact on Afghani women. In addition, she describes the horrors women faced under the Taliban regime and outlines the continued challenges that they face in post-Taliban Afghanistan as well as RAWA’s response ...